Thermal energy performance due to convection process of nanofluid in a porous medium due to split lid motion in a right triangular enclosure. Issue 3 (13th May 2022) - Ullah, M Zaka; Hussain, S T; Haq, Rizwan Ul; Alzahrani, A Khamis; Mallawi, Fouad
Abstract: In the current phenomena, a study is carried out for the convection process of nanofluid within the porous media enclosed in a triangular permeable cavity. The heat generation effect within the nanofluid is developed when the two heat sources are applied through the split lids. To analyse the behaviour of nanofluids and steam lines, we have considered an elliptic (cold, adiabatic, and heated)-shaped obstacle that is placed inside the cavity. Mathematical modelling is carried out through continuity, momentum equation, and energy equations in the form of a system of non-linear partial differential equations. These equations are produced after incorporating the relations of viscosity, density, shapes of nanoparticle, and thermal conductivity for nanofluids Constraints are adjusted according to the forced convection due to the upper moving wall of the cavity. Four different cases of the upper double lid-driven wall are considered. All the emerging parameters, namely Reynolds number ( 25 Re 750 ), heat generation ( - 10^4 Q 40 ), nanoparticle volume fraction ( 0 φ 0.2 ), and Darcy number 10^ - 5 Da 10^ - 3, are analysed through variation of velocities, temperature profile, isotherms, and streamlines. Various cases at the surface of the inner elliptical obstacle provide significant contributions in the variation of heat transfer rate and velocity profiles. Nanoparticles provide a considerable increase in the heat transfer rate. The Darcy number shows the substantial variation in the formation of the isothermal region. An increase in heat generation parameter Q provides an improvement in temperature distribution inside the cavity and it also caused the formation of a single isothermal region around the heated obstacle. Graphical Abstract: